2018
DOI: 10.4254/wjh.v10.i10.685
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional support in chronic liver disease and cirrhotics

Abstract: The liver is a major organ and an essential component in maintaining an appropriate nutritional status in healthy individuals through metabolism of protein, carbohydrates, and fat. In individuals with chronic liver disease (CLD), along with a number of other essential functions that the liver serves, its role in nutrition maintenance is severely impaired. Common causes of CLD include hepatitis C, alcoholic liver disease, and non-alcoholic liver disease. Amongst this population, the most common manifestation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
31
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 42 publications
1
31
0
5
Order By: Relevance
“…The liver plays an important role in the metabolism of carbohydrates, proteins and fat (25,26) . Dysfunction of the liver contributes to malnutrition, which can develop occultly in the early stage of chronic liver disease and can ultimately lead to protein-energy malnutrition (6,7) . The identification of patients at risk of malnutrition in a hospital setting with an effective and simple nutrition risk screening tool is essential; such a tool would enable earlier nutrition assessment and more timely interventions, leading to reductions in morbidity and mortality in patients with cirrhosis (6) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The liver plays an important role in the metabolism of carbohydrates, proteins and fat (25,26) . Dysfunction of the liver contributes to malnutrition, which can develop occultly in the early stage of chronic liver disease and can ultimately lead to protein-energy malnutrition (6,7) . The identification of patients at risk of malnutrition in a hospital setting with an effective and simple nutrition risk screening tool is essential; such a tool would enable earlier nutrition assessment and more timely interventions, leading to reductions in morbidity and mortality in patients with cirrhosis (6) .…”
Section: Discussionmentioning
confidence: 99%
“…Dysfunction of the liver contributes to malnutrition, which can develop occultly in the early stage of chronic liver disease and can ultimately lead to protein-energy malnutrition (6,7) . The identification of patients at risk of malnutrition in a hospital setting with an effective and simple nutrition risk screening tool is essential; such a tool would enable earlier nutrition assessment and more timely interventions, leading to reductions in morbidity and mortality in patients with cirrhosis (6) . Previous European studies suggested that the RFH-NPT was more sensitive than the NRS-2002 for the assessment of the risk of malnutrition and the prediction of disease progression and outcomes in patients with chronic liver disease based on regression analysis (11,12,16,17) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Protein‐calorie malnutrition is frequent in advanced chronic liver disease (ACLD), ranging from 20% to 60%, depending on the stage of the disease; it is related to higher morbidity and mortality ( 1 ) . Its pathogenesis is multifactorial; reduced dietary intake, nutrient malabsorption, anabolic resistance and increased energy expenditure are causes associated with malnutrition in these patients ( 2 ) .…”
Section: Introductionmentioning
confidence: 99%
“…2 Malnutrition in HCV is associated with increased mortality and morbidity. [3][4][5] The pathology of liver disease significantly alters digestion, absorption, storage, and metabolism of macronutrients and micronutrients. Anorexia, nausea, vomiting, and other gastrointestinal (GI) symptoms can lead to poor dietary intake and perpetuate the risk of malnutrition.…”
Section: Introductionmentioning
confidence: 99%